2011
DOI: 10.3892/ijo.2011.1317
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin enhances bortezomib-induced cytotoxicity via endoplasmic reticulum stress-mediated CHOP (GADD153) induction and autophagy in breast cancer cells

Abstract: The specific 26S proteasome inhibitor, bortezomib (BZ) potently induces apoptosis as well as autophagy in metastatic breast cancer cell lines such as MDA-MB-231 and MDA-MB-468. The combined treatment of clarithromycin (CAM) and BZ significantly enhances cytotoxicity in these cell lines. Although treatment with up to 100 μg/ml CAM alone had little effect on cell growth inhibition, the accumulation of autophagosomes and p62 was observed after treatment with 25 μg/ml CAM. This result indicated that CAM blocked au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 51 publications
(75 reference statements)
2
30
0
Order By: Relevance
“…We initially confirmed that AZM and CAM inhibit autophagy in HNSCC cell lines as previously described in myeloma and breast cancer cell lines by flux analysis [12, 14, 18]. The conversion from the soluble cytosolic LC3B-I with a molecular weight of 16 kDa to the membrane-bound LC3B-II with a molecular weight of 18 kDa via the conjugation of phosphatidyl ethanolamine represents the formation of autophagosomes.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…We initially confirmed that AZM and CAM inhibit autophagy in HNSCC cell lines as previously described in myeloma and breast cancer cell lines by flux analysis [12, 14, 18]. The conversion from the soluble cytosolic LC3B-I with a molecular weight of 16 kDa to the membrane-bound LC3B-II with a molecular weight of 18 kDa via the conjugation of phosphatidyl ethanolamine represents the formation of autophagosomes.…”
Section: Resultssupporting
confidence: 67%
“…In multiple myeloma and breast cancer cells, we found that apoptosis induction was enhanced by the proteasome inhibitor bortezomib and AZM or CAM combination treatment together with endoplasmic reticulum (ER)-stress loading [12, 14]. In terms of drug-repositioning, AZM and CAM are considered strong candidates as clinical autophagy inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ER-stress-mediated CHOP induction is involved in the cytotoxicity of BZ in various kinds of cells (10,33,34). This was also supported by data indicating that translational inhibition using cycloheximide attenuated BZ-induced cytotoxicity in U266 cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This agent has been shown to enhance endoplasmic reticulum stress-mediated apoptosis when combined with bortezomib, a proteasome inhibitor, although CAM has shown to only be efficacious when administered in a combination regimen in breast cancer and myeloma cells [177, 178]. In another study, the combination of HDACi SAHA, with bortezomib and CAM, induced apoptosis in breast cancer cells.…”
Section: Pathways Involved In Tumour Growthmentioning
confidence: 99%